DİSTRİBUTİON DES ÉLÉMENTS TRACES MÉTALLİQUES DANS LES SOLS AVOİSİNANT LA CİMENTERİE DE BOUSKOURA-MAROC DISTRIBUTION OF TRACE METALS IN SOILS AROUND THE BOUSKOURA CEMENT PLANT MOROCCO - Saber, Najib; Chemsi, Zakaria; Zaakour, Fatna; Matech, Fatimaezzahra; Moustarhfer, Kaoutar; Mohcine, Hajar (European Scientific Journal, ESJ, 2014)
To appreciate the impact of dust from Bouskoura cement plant on the agricultural soils quality, analysis of agronomic parameters (pH, organic carbon and CaCO3) and metallic trace elements was assessed (Cd, Cu, Ni, Pb, Zn). Eighty samples was taken fromhorizons [0-10cm] and [10-20cm]. The most important results show that the alkalinity of soils rich in CaCO3is linked to cement dust emission, and highlight an significant spatial variation of pH, CaCO3, Pb and Zn. The results also infer that the soils quality is affected by dust emitted from the cement and practiced agriculture. These soilsshow Ni anomaliesin some plots at different stations, Cd anomaliesin the various stations and Znanomalies at station I, II and III.